2004
DOI: 10.1007/s00401-004-0920-5
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy case of hereditary diffuse leukoencephalopathy with spheroids, clinically suspected of Alzheimer?s disease

Abstract: We report here a case of orthochromatic leukodystrophy with spheroids. A 40-year-old woman developed forgetfulness. About 1 year after the onset, clinical examination confirmed global intellectual deterioration with amnesia, spatiotemporal disorientation, and impairment of judgment. At age 43, she experienced tonic-clonic convulsions several times, and died of pneumonia at the age of 44. Alzheimer's disease was suspected clinically. Pathologically, there was severe diffuse demyelination of the deep white matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 7 publications
5
40
0
Order By: Relevance
“…HDLS is neuropathologically characterized by the extensive loss of myelin sheaths, axonal destruction and the presence of numerous axonal spheroids, pigmented macrophages and astrogliosis (2,(9)(10)(11)(12)(13)(14). These changes were clearly observed in the centrum semiovale of the cerebral white matter in one of our patients (patient 2) (8).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…HDLS is neuropathologically characterized by the extensive loss of myelin sheaths, axonal destruction and the presence of numerous axonal spheroids, pigmented macrophages and astrogliosis (2,(9)(10)(11)(12)(13)(14). These changes were clearly observed in the centrum semiovale of the cerebral white matter in one of our patients (patient 2) (8).…”
Section: Discussionmentioning
confidence: 68%
“…Corpus callosum atrophy (CCA) has been noted in the postmortem examinations of advanced HDLS patients with diffuse widespread WMLs and severe brain atrophy (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…DISCUSSION Our report describes the MRI pattern of HDLS in patients with CSF1R gene mutations. MRI findings in patients with HDLS have been described previously in 20 reports, 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] however, without knowledge of the CSF1R gene mutation carrier status. 4 We developed an HDLS MRI severity scoring system, modified from those devised for X-ALD, Krabbe disease, and MLD.…”
Section: Resultsmentioning
confidence: 81%
“…7,8,[13][14][15][16][17][21][22][23][24][25] The clinical presentation in POLD family FTD368 included symptoms of depression, abnormal behavior, and an inability to function, progressing to dementia in the 3 siblings from the second generation. The proband Figure 3 Functional effects of CSFR1 mutations in cell culture CSF-1 treatment leads to autophosphorylation of wild-type but not mutant CSF1R.…”
mentioning
confidence: 99%
“…4,7,16,24,28 The white matter atrophy and myelin loss is similar in patients with pathologically confirmed HDLS; however, axonal spheroids are prominent in affected white matter in addition to myelinated fiber loss, gliosis, and pigment-laden glial cells. 3,8,9,23,25,29 However, they can be sparse in areas of white matter with burnt-out pathology and few residual axons, and must be sought for in areas where the white matter pathology is ongoing. In a study of the originally described POLD family in 1936, it was reported that axonal dilations consistent with axonal spheroids were present in the affected brain tissue.…”
mentioning
confidence: 99%